PERBANDINGAN MODEL PEMBELAJARAN INQUIRY DAN DISCOVERY TERHADAP HASIL BELAJAR KOGNITIF SISWA KELAS X PADA MATA PELAJARAN BAHASA INDONESIA - Widy Wafiq Lestari; Hadi Gunawan Sakti; Muzakkir Muzakkir (Comm-Edu (Community Education Journal), 2026)
This study aims to analyze the comparative effectiveness of Inquiry and Discovery learning models on students’ cognitive learning outcomes in Grade X Indonesian language classes at SMKN 3 Mataram. The research employed a quantitative approach using a quasi-experimental method with a one-group pretest–posttest design. The sample consisted of 30 students selected through simple random sampling. Data were collected using a 30-item multiple-choice test as the main instrument, supported by observation and documentation. Data were analyzed using a paired sample t-test at a 5% significance level. The results showed that the Inquiry model increased the mean score from 59.5 (pretest) to 70.8 (posttest), with a t-value of 76.40, while the Discovery model increased the mean score from 59.8 to 75.7, with a t-value of 113.90. Both models significantly improved students’ cognitive learning outcomes since the calculated t-values exceeded the t-table value (1.699). However, the Discovery model demonstrated a higher improvement compared to the Inquiry model. These findings indicate that student-centered learning models based on constructivist principles are effective in enhancing cognitive achievement, with Discovery Learning showing greater effectiveness in the context of Indonesian language learning at the vocational high school level.